PPI in Poor Countries : How to Increase Private Participation in Infrastructure Management and Investment - Leigland, James (World Bank, Washington, DC, 2012)
To overcome huge shortfalls in access to infrastructure services, poor countries need much higher investment levels and more expertise to build, operate, and maintain infrastructure facilities. The private sector is one source for such resources, and projects involving private participation in infrastructure (PPI) have increasingly been used in developing countries. But PPI investment has been much lower in poor countries than in better-off developing countries-and has been more affected by the global financial crisis. How can PPI projects play a larger role in improving infrastructure service provision in these countries?